Development and Validation of Diagnostic Tool for Janu Sandhigata Vata with Special Reference to Knee Osteoarthritis- Mixed-Method Diagnostic Validation Study Protocol - Hemlata Shete; Suhas Kumar Shetty; Sarang Shete (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: In Ayurveda, emphasis is placed on proper diagnosis before giving treatment. A proper diagnosis involves comprehensive assessment of multiple factors like Dosha, Dhatu etc. This personalized framework is influenced by physicians' perception there causing variability in clinical judgement. Standardization, reproducibility, and objectivity of diagnostic tools are increasing and contemporary science has well established it. Unlike Ayurveda which relies on classical texts and physicians’ expertise. This gap creates challenges in ensuring uniformity in diagnosis, especially in clinical research, interdisciplinary practice and evidence- based validation. Development of diagnostic tool is needed to bridge this gap and enhance the credibility of Ayurvedic diagnosis. Sandhigata vata is a leading disease treated in Ayurveda and diagnosed based on Laxana due to vata vitiation. No standard diagnostic tool is available for it. Objective: To diagnose osteoarthritis using Ayurvedic and modern diagnostic approaches and to develop and validate a standardized diagnostic tool/process for Janu Sandhigata Vata. Methodology: The study will be conducted in four phases. Phase I will identify questionnaire items and response options through literature review, survey, focus group discussions, and in-depth interviews. Phase II will involve pre-testing of the items and response scales among Ayurveda physicians and patients with Janu Sandhigata Vata. Phase III will involve domain reduction and expert item revision to retain relevant items and remove unsuitable ones. Phase IV will assess the validity and reliability of the developed diagnostic tool. Both qualitative and quantitative methods will be employed, followed by appropriate statistical analysis. Results: In January 2025 present study was initiated. It includes both qualitative and quantitative Methods. All four phases followed by statistical analysis is expected to be completed by June 2027. Conclusion: This study protocol is designed to develop and validate a diagnostic tool/ process and develop standard methodology to diagnose diseases in Ayurveda.